2020
DOI: 10.1080/13880209.2020.1738503
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits ACHN cells via regulation of histone acetylation

Abstract: Context: The relationship between resveratrol and histone acetylation in renal cell carcinoma (RCC) has not yet been reported. Objective: To explore the functional role of resveratrol in RCC. Materials and methods: Functional experiments were performed to determine proliferatio n of ACHN cells with treatment of resveratrol (0, 7.8125, 15.625, 31.25 and 62.5 lg/mL, for 12, 24 and 48 h of culture) or 0.1 lM SAHA. The enzyme activities of MMP-2/-9 were measured by gelatine zymography and histone acetylation by We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Some patients cannot persist and the long-term effect is not good [19]. Modern researches have shown [20] that Chinese medicine-assisted RCC postoperative treatment has a relatively clear role in improving patients' clinical symptoms, protecting renal function, regulating body immunity, preventing tumor recurrence and metastasis, and improving the quality of life of patients. Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients cannot persist and the long-term effect is not good [19]. Modern researches have shown [20] that Chinese medicine-assisted RCC postoperative treatment has a relatively clear role in improving patients' clinical symptoms, protecting renal function, regulating body immunity, preventing tumor recurrence and metastasis, and improving the quality of life of patients. Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive Component Disorders References upregulation of DNMT omega-3 fatty acids: DHA, EPA colorectal cancer [25,26] folic acid colorectal cancer, breast cancer [27,28] methionine lung cancer [29] vitamin A congenital heart defects [30] DNA methyltransferase inhibition kaempferol bladder cancer [31] gallic acid lung cancer and oral cancer [32] epigallocatechin-3-gallate breast cancer, diabetic kidney disease [33,34] β-caroten colorectal cancer [35] sulforaphane breast cancer, cardiomyopathy [36,37] omega-3 fatty acids: EPA hepatocarcinoma [38] vitamin A congenital heart defects [30] histone deacetylase inhibition resveratrol breast cancer, renal cell carcinoma, colorectal cancer [39][40][41][42] apigenin prostate cancer, lung cancer [43,44] luteolin lung cancer, leukemia [45,46] chrysin melanoma [47] cinnamic acid derivatives colon and cervical cancer [48] gallic acid prostate cancer, cardiovascular diseases [49] epigallocatechin- Epigallocatechin-3-gallate (EGCG), a polyphenol member, can reduce global DNA methylation levels, DNA methyltransferase (DNMT) activity, messenger RNA (mRNA), and protein levels of DNMT1, DNMT3a, and DNMT3b. EGCG can directly inhibit the DNMT catalytic site.…”
Section: Mechanismsmentioning
confidence: 99%
“…Compared with synthetic drugs, treatment with natural products have fewer side effects, while exhibiting favorable outcomes ( 13 ). Although other studies have reported that several natural products, such as Epigallocatechin Gallate ( 19 ), quercetin ( 20 ), englerin A ( 21 ), honokiol ( 22 ), curcumin ( 23 ) and resveratrol ( 24 ) have shown beneficial results in preclinical studies of RCC, the research on the mechanism of the therapeutic activities of natural products on RCC is remains limited. The present study examined the antitumor effects of natural products on RCC.…”
Section: Discussionmentioning
confidence: 99%